Use of Ecosystem Services of Sarcocephalus latifolius (Sm.) E.A.Bruce and Induced Effect of Human Pressure on the Species in the Southwestern Region of Burkina Faso - Kaboré, Sibiry Albert; Hien, Mipro; Ouédraogo, Dénis; Diallo, Tiéoudia Rebecca Elodie; Hahn, Karen; Nacro, Hassan Bismarck (Ethnobotany Research and Applications, 2014)
<!--[if gte mso 9]> Normal 0 21 false false false FR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tableau Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> People depend heavily on natural resources for their daily living. In the Sudanian zone of Africa characterized by high population growth and poverty incidence, there is a growing pressure on high value species such as Sarcocephalus latifolius (Sm.) E.A.Bruce. The objectives of this study were to evaluate its diverse uses and to highlight some practices which could affect its survival. The work was conducted in the southwestern region of Burkina Faso with a sample of 360 respondents. Data were analyzed using three indexes. The results show that S. latifolius is used for 80 use-types belonging to seven use categories. The use of roots to treat stomachaches has a consensus value for use-types of 0.357 and is the most important use of the species in medicine. The fact that roots are the most often used plant part constitutes an aggravating factor for the survival of this species in the semi-arid context.